Variegated mud-loving beetles (Heteroceridae) of Russia and adjacent countries: Additions and corrections to the Catalogue of Palaearctic Coleoptera, Volume 3 (2016) - Sazhnev, Alexey S. (Zootaxa, 2020)
An analysis of all available information on the variegated mud-loving beetles (Heteroceridae) of Russia and adjacent countries published in the 2nd edition of the third volume of the Catalogue of Palaearctic Coleoptera is presented. An annotated list based on collections and literature is given of new records and new taxonomic data on 31 species of variegated mud-loving beetles.